Hair Calcium and CardiovascularDisease - Mohan, S.; Durairaj, K.S.P.; Arjunan, V.; Karthikeyan, B.; James Jabaseelan Samuel, E. (Asian Journal of Chemistry, 2010)
The determination of major, minor and trace elements in human hair shows high promise in clinical medicine and toxicology for the easy detection of diseases. In particular, the elemental analysis of human hair is becoming popular for the identification of the major element calcium in human hair samples in connection with ischaemic heart disease. Hence, an attempt has been made in the present work to investigate calcium concentration in human hair, particularly in patients suffering from coronary heart diseases through atomic absorption spectrophotometry and X-ray studies. It is concluded from the results that the south Indian partients suffering from myocardial infarction belong to the low calcium concentration peak while in healthy population the calcium level in hair is high.